Physical Quantities of Reissner-Nordström Spacetime with Arbitrary Function and Regularized Procedure - Gamal G. L. Nashed (Advances in High Energy Physics)
We use the covariant teleparallel approach to compute the total energy of a spherically symmetric frame with an arbitrary function, that is, ℑ(r). We show how the total energy is always effected by the inertia. When use is made of the pure gauge connection, teleparallel gravity always yields the physically relevant result. We also calculate the total conserved charge and show how inertia spoils the physics in the time coordinate direction. Therefore, a regularized expression is employed to get a plausible value of energy. Finally, we use the Euclidean continuation method, in the context of TEGR, to calculate the energy, Hawking temperature, entropy, and first law of thermodynamics.